The Influence of Parental Involvement on Parent Satisfaction: The Moderating Effect of Parental Educational Level and the Number of Children - Shao, Mingming; He, Wei; Zhao, Li; Su, Yu-Sheng (Frontiers in Psychology, 2022)
With the change in the location of school education from the classroom to the home during the COVID-19 outbreak, there should be more educational caregiving from children’s parents when children learn online. Parental involvement in children’s online learning including study guide and psychological counseling is the specific content of educational caregiving, which is different from face-to-face learning. More attention should be paid to parental involvement and parents’ satisfaction with the online learning effect. This study therefore conducted a survey on middle school students’ parents to establish a moderating model, exploring the influence of parental involvement on parent satisfaction, and the number of children and parental education level as the moderator variables influencing parental involvement. The results show that there is a significant positive correlation between parental involvement and satisfaction, while the parental education level and the number of children both have a moderating effect on the relationship between parental involvement and parent satisfaction. The moderating effect of the education level of parents shows negative, while the moderating effect of the number of children is positive. An interesting finding is that the number of children has a very low influence on parental involvement.